Timing and duration of discrete tectono-metamorphic events of the polymetamorphic high-grade Central zone of the Limpopo Belt (South Africa): Insight from in situ geochronology of monazite and zircon - Zhou, Tian; Klemd, Reiner; Brandt, Sönke; Liu, Yu; Li, Qiu Li (Precambrian Research, 2022)
The Central Zone of the Limpopo Belt in southern Africa is a complex polymetamorphic terrane that has experienced three metamorphic events, at 3.22 Ga (M1), 2.71–2.56 Ga (M2) and 2.02 Ga (M3). On the basis of a previous detailed petrological and geothermobarometrical study of a newly discovered supracrustal enclave within the Bulai Pluton (ca. 2.61 Ga granitoid gneiss in the Central Zone), we conducted a geochronological in situ study of texturally and chemically different monazite and zircon grains, which occur respectively as inclusions in garnet, in decompressional cordierite coronas around garnet and as matrix grains in polymetamorphic granulite-facies metapelites. Secondary-ion mass spectrometry (SIMS) in situ analyses of the monazite and zircon grains in thin sections, complemented by analyses of separated zircon grains, allowed the texturally-controlled direct determination of U-Pb and 207Pb/206Pb ages at a scale of < 10 μm. A concordant age of ca. 2.71 Ga derived from zircon included in garnet is interpreted to reflect the age of initial garnet growth during the prograde M2 metamorphism. Zircons in the cordierite coronas around garnet revealed a slightly younger concordant age of ca. 2.56 Ga. Zircon growth in the coronas is related to the retrograde breakdown of garnet (Zr-bearing) through to the decompression reaction garnet + sillimanite + quartz → cordierite + zircon and hence the ca. 2.56 Ga zircon age is interpreted to reflect the timing of post-peak decompressional uplift. The zircon ages constrain the duration of M2 metamorphism to approximately 145 Myr. A concordant 2.71 Ga age of large monazite inclusions in garnet cores corroborates the 2.71 Ga zircon age of initial garnet growth during the prograde M2 metamorphism. Core domains of the largest monazite in cordierite corona revealed ages between 2.5 and 2.0 Ga that are interpreted to reflect (multiple) Pb-loss during the M3 granulite-facies metamorphism. Other monazites in cordierite coronas and matrix showed an age of ca. 2.0 Ga, reflecting complete re-equilibration or new growth during M3 overprinting. Owing to the preservation of the original micro-textures related to the growth of zircon and monazite we were able to link the age data with the P-T record, and refine the timing and duration of the M2 granulite-facies metamorphism (approximately 2.71–2.56 Ga) in the Limpopo Belt that was previously dated at ca. 2.62 Ga by zircon separation techniques. The ca. 145 Ma duration of granulite-facies metamorphism is consistent with a tectonic model of long-lasting asthenosphere upwelling and subsequent continent–continent collision in the late Neoarchean. Decompression triggered by post-collisional extension occurred at 2.56 Ga. Paleoproterozoic M3 granulite-facies metamorphism at ca. 2.0 Ga caused the widespread re-setting of the U-Pb and Pb-Pb data that also affected most zircon and monazite grains. This study reveals that precise dating of the timing and duration of distinct tectono-metamorphic events by texturally-controlled in situ geochronology allows a much better insight into the complex geodynamic evolution of high-grade polymetamorphic terranes.
CRIS-Team Scopus Importer:2022-01-21
Keywords: Duration of metamorphic events; Limpopo Belt; Monazite; Polymetamorphism; Secondary ion mass spectrometry; U-Pb dating; Zircon